The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1111/j.1475-6811.2009.01219.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental shame and guilt: Distinguishing emotional responses to a child's wrongdoings

Abstract: This research differentiates shame and guilt as distinct emotional reactions that parents in the United States can have for their children's misdeeds. In Study 1, when 93 parents wrote about their child's worst transgression, their ratings of perceived public exposure and threat to their self‐image predicted shame, whereas the degree to which they felt a lack of control over their child and believed the act harmed others predicted guilt. In Study 2, when 123 mothers rated their reactions to an imagined wrongdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 36 publications
0
47
1
2
Order By: Relevance
“…The shame-causes-devaluation link seems unlikely. The experimental manipulation of criticism and publicity reliably boosts shame (23,38,62,63). In contrast, displays of shame or embarrassment attenuate an audience's devaluing response when the audience and the offender share common knowledge about the discrediting act (35,64,65).…”
Section: Discussionmentioning
confidence: 99%
“…The shame-causes-devaluation link seems unlikely. The experimental manipulation of criticism and publicity reliably boosts shame (23,38,62,63). In contrast, displays of shame or embarrassment attenuate an audience's devaluing response when the audience and the offender share common knowledge about the discrediting act (35,64,65).…”
Section: Discussionmentioning
confidence: 99%
“…Less crippling, and often more conscious, guilt tends to prompt approach behaviors such as making amends, apologizing, or confessing (Tangney et al, 1996), as well as prompting selfreflection, action, and motivation (Blum, 2008). Unlike shame, guilt has been linked to the capacity for empathy (Oppenheim, 2008;Scarnier et al, 2009), so parents experiencing guilt may have more ability to reflect on their child's experiences (Chazan, 2003;Green, 2000). Though guilt is painful, in parents it is also an empirical predictor of more adaptive parenting strategies involving less aggression and less removal of warmth (Scarnier et al, 2009).…”
Section: Guiltmentioning
confidence: 97%
“…Narcissism is related to the capacity for empathy, a key parental function that is crucial for child therapists to help parents develop during parent work. Interestingly, researchers have shown that shame-ridden parents tend to display less empathy and less warmth (Scarnier, Schmader, & Lickel, 2009). Mature empathy requires autonomy, so that the parent can reflect on the child's experience while remaining separate from it (Chazan, 2003).…”
Section: Shamementioning
confidence: 97%
See 2 more Smart Citations